Antifungal Inhibitory Activity Test of Papaya Leaf (Carica papaya L.) Ethanol Extract Against the Growth of Trichophyton mentagrophytes - Intan Permata Rambin Siregar; Febrina Dewi Pratiwi Lingga (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2026)
Background: Trichophyton mentagrophytes is one of the dermatophyte species that commonly infects keratin-rich tissues such as hair, skin, and nails. These infections may lead to various forms of tinea and remain a significant health concern. Meanwhile, papaya (Carica papaya L.) is widely recognized as a medicinal plant traditionally used in various treatments. Papaya leaves contain several bioactive compounds, including alkaloids, flavonoids, saponins, and tannins, which are considered to have potential antifungal activity. Therefore, papaya leaves are regarded as a promising subject for further investigation as an alternative therapeutic option for dermatophyte infections. Purpose: To determine the inhibitory effect of ethanol extract of papaya leaves (Carica papaya L.) on the growth of Trichophyton mentagrophytes.  Methods: This study employed a quantitative experimental method with a posttest-only control group design, using treatments of ethanol extract of papaya leaves (Carica papaya L.) at concentrations of 30%, 40%, and 50%, along with itraconazole (positive control) and DMSO (negative control). The test used potato dextrose agar and the disk diffusion method to observe the concentrations that affect the growth of Trichophyton mentagrophytes. Result: It was proven that ethanol extract of papaya leaves (Carica papaya L.) at concentrations of 30%, 40%, and 50% could inhibit the growth of Trichophyton mentagrophytes. Conclusion: Ethanol extract of papaya leaves (Carica papaya L.) has potential as an antifungal agent against Trichophyton mentagrophytes. The 50% concentration showed the greatest inhibitory effect compared to the 30% and 40% concentrations.